Analysis of the Urban Mobility Master Plan of Garça/SP: Compliance with National Policy Guidelines and Local Challenges - Gonçalves , Guilherme Henrique Brunhare; Magagnin, Renata Cardoso; Fontes, Maria Solange Gurgel de Castro (Technical and Scientific Journal Green Cities, 2025)
Objective – To analyze Law No. 5.558/2023, which establishes the Urban Mobility Master Plan of Garça/SP, assessing its compliance with Federal Law No. 12.587/2012 and the guidelines of PlanMob, with a focus on the needs and challenges of small cities. Methodology – The study adopted an exploratory and descriptive approach to analyze Garça/SP’s Urban Mobility Master Plan. The evaluation was based on indicators proposed by Magagnin (2023), aligned with Federal Law No. 12.587/2012, and focused on thematic axes related to transport systems and sustainable urban mobility. The presence of these themes in the legal text was verified through manual content analysis, classifying each parameter as fully addressed, partially addressed, or absent. Annexes containing technical information were considered complementary and not included in the direct evaluation. Originality/Relevance – The study addresses a theoretical gap concerning the scarcity of systematic analyses on the implementation of the National Urban Mobility Policy (PNMU) in small cities, which have dynamics and limitations distinct from large urban centers. Most research focuses on metropolises or medium-sized cities, neglecting the specific challenges of smaller municipalities, such as limited public transport provision and the absence of regulations for essential services, including school or rural transport. The academic relevance lies in contributing to urban planning by demonstrating how municipal legal instruments may or may not incorporate federal guidelines, strengthening the discussion on sustainable urban mobility, territorial inclusion, and equity in public policies across different urban scales. Results – Of the 24 parameters analyzed in Garça/SP’s Urban Mobility Master Plan, 11 (45.8%) fully comply with the National Urban Mobility Policy (PNMU), 6 (25.0%) are partially addressed, and 7 (29.2%) are not addressed. The main gaps concern public transport, modal integration, fare policy, specific services, environmental impacts, and accessibility in rural areas, indicating the need for greater detail in these aspects. Theoretical/Methodological Contributions – The study proposes a replicable methodology for evaluating municipal plans based on normative indicators, contributing to the academic debate on urban planning in small cities and their compliance with national policies. Social and Environmental Contributions – The study identifies pathways to improve urban mobility in smaller cities, focusing on inclusion, accessibility, and sustainability, highlighting measures that can reduce inequalities in transport access and mitigate environmental impacts.